Determinan Faktor yang Berpengaruh terhadap Kejadian Phlebitis di Rumah Sakit Bunda Pengharapan Merauke - Anneke Rumbewas; Blasius deddy; Julvainda Julvainda (Jurnal Sehat Mandiri, 2024)
Phlebitis is nosocomial infection caused by microorganisms in patients during hospitalization, resulting in clinical symptoms that last at least 24 hours. The purpose was to determine the effect of determinant factors on the incidence of phlebitis. This type of research is observational using a case control design with a quantitative approach. This research was conducted at Bunda Pengharapan Hospital, Merauke. This research was conducted from April to May 2024. The sampling technique used purposive sampling and amounted to 40 respondents. The instruments used were questionnaires related to phlebitis that had been tested for validity (0.6) and reliability (0.911), as well as patient medical records. Bivariate analysis using the chi-square test and logistic regression. Factors affecting phlebitis are comorbidities, with p=0.003, infusion treatment, p=0.000 and duration of infusion, p=0.001, type of fluid, p=0.003 and dressing material, p=0.000, washing hands according to SOP, p=0.000, treatment status (repeated or new), with p=0.004. Infusion treatment factors P=0.021 and OR=22.726, meaning that the infusion treatment factor has an effect 22.7 times greater than other factors. In conclusion, only 7 factors are significant to the incidence of phlebitis, only 7 factors are significant, including comorbidities, infusion treatment, duration of infusion, type of fluid, dressing material, washing hands according to SOP, treatment status. The clinical implication was important for health workers to pay attention to these factors in an effort to prevent phlebitis in patients.